Canada’s rapid research response to the COVID-19 pandemic: A bibliometric analysis - Stojanovic, Vanja (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2021)
This study assesses the nature of Canada’s rapid research response through term and keyword bibliometric analysis. The following asks: What are the major areas of COVID-19 rapid research output conducted in Canada during the first five and half months of 2020, and how can the results of this analysis inform future accelerated research efforts toward an effective response to infectious disease emergencies? The results suggest that infection prevention, epidemiology, therapeutics, and public health strategies were among the top-producing research areas in Canada during the onset of the pandemic. Moreover, the analysis reflects gaps in the literature addressing diagnostics and vaccine development.